Isolasi Staphylococcus aureus dari Swab Tangan Penjamah Makanan di Kantin Universitas Mataram - Hasbi, Nurmi; Rosyunita; Rahim, Adelia Riezka; Ayunda, Rahmah Dara (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
One of the main qualities of food is seen from the biological safety aspect, such as being free from Pathogenic microorganisms. Staphylococcus aureus is a pathogenic bacterium that can contaminate food ingredients come from the skin of food handlers. S. aureus produces enterotoxins that have a poisoning in consumers.The preliminary observationstated that there were still many food handlers in the Mataram University canteen who did not pay attention to hand hygiene and personal sanitation. This study aims to determine the bacterial contamination of S. aureus swabbed from the hands of food handlers in the Mataram University cafetaria. The method was used in this research is descriptive observational. The research consisted of two stages, namely isolation and biochemical identification. The isolation stage resulted 10 culturable bacterial isolates. All bacteria were able to ferment mannitol on Mannitol Salt Then, the biochemical test identification resulted that all isolates had a positive catalase test, a positive slide coagulase test, Gram-positive, and staphylococci cell. The TSIA test resulted A/A or (acid)/(acid) which indicated that all isolates were able to use diverse carbon sources from sucrose, lactose, glucose. Moreover, other test as sulfur, indole and motility tests were negative. Therefore, all isolates in this study are classified as S. aureus. This research is also a promotive and preventive effort for the campus in implementing hygiene and sanitation for food handlers in the cafetaria.